Algorithms, Engagement, and Sales: Short-Form Video Metrics as Predictors of Purchase Intention - Muhammad Faisal; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
The rapid growth of short-form video platforms has reshaped digital marketing practices and consumer purchasing behavior. This research explores how algorithmic recommendation and content engagement influence purchase intention through perceived arousal within the Stimulus-OrganismResponse framework. A quantitative survey approach was employed and analyzed using regression analysis. The findings indicate that algorithmic recommendation and content engagement significantly affect perceived arousal, which subsequently influences purchase intention. The results highlight the importance of emotional arousal as a key mechanism in transforming digital stimuli into consumer behavioral responses. The study suggests that optimizing recommendation systems and developing engaging content can enhance conversion outcomes in short-form video marketing environments.